2005
DOI: 10.2135/cropsci2005.0792
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘Doyce’ Hulless Barley

Abstract: Registration of 'Oklee' Wheat relatively early maturing and produces spikes 1.3 d earlier 'Oklee' is a hard red spring wheat (Triticum aestivum L.) than 2375 and 0.6 d earlier than Oxen (PI 596770), the most (Reg. no. CV-963, PI 634553) developed and released by the widely grown cultivar in Minnesota since the late 1990s. Oklee Minnesota Agricultural Experiment Station in cooperation is a semidwarf cultivar and averages 75 cm, the same height with USDA-ARS in January 2003. It was named after a town as Oxen, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Strider is a six‐row, covered feed barley released by the Oregon Agricultural Experiment Station in 1997. Doyce is a six‐row, naked feed barley with winter growth habit, released by the Virginia Agricultural Experiment Station (Brooks et al, 2005).…”
mentioning
confidence: 99%
“…Strider is a six‐row, covered feed barley released by the Oregon Agricultural Experiment Station in 1997. Doyce is a six‐row, naked feed barley with winter growth habit, released by the Virginia Agricultural Experiment Station (Brooks et al, 2005).…”
mentioning
confidence: 99%
“…Doyce (PI 634932) was the first hulless cultivar developed by the Virginia Tech barley breeding program and represented the highest yield potential for hulless barley at the time of its release in 2003 (Brooks et al, 2005c). Doyce (PI 634932) was the first hulless cultivar developed by the Virginia Tech barley breeding program and represented the highest yield potential for hulless barley at the time of its release in 2003 (Brooks et al, 2005c).…”
Section: Methodsmentioning
confidence: 99%
“…In a review of western Canadian barley cultivars released from 1910 to 1987, the authors concluded that yield improvement was associated with increased harvest indices and reduced lodging rather than to a change in specific yield components ( Jedel and Helm, 1994). Additional information for barley cultivars used to develop these populations can be found in the following citations: Jensen (1964aJensen ( , 1964b, Caldwell et al (1966), Finker et al (1968, Starling et al (1970Starling et al ( , 1973, Graham et al (1982), and Brooks et al (2005aBrooks et al ( , 2005bBrooks et al ( , 2005c. Rasmusson and Cannell (1970) demonstrated that spikes per square meter was consistently associated with yield while the effectiveness of selection for kernel weight and VA93-42-57 were derived from a series of crosses comprising CI 9623, CI 9658, CI 9708, barley yellow dwarf virus-resistant 'Atlas'/'Hanover' (CI 13197), or 'Rapidan' (CI 14006)/4/'Harrison' (CIho 10667)/3/Cebada Capa/Wong//awnleted selection of Hudson/5/'Barsoy' (CI 11904).…”
mentioning
confidence: 99%
“…Breeding efforts are focused on improving these traits. Current releases and experimental lines offer higher yield, higher test weight, and better dehulling than those previously available (2).…”
Section: Hulless Barleymentioning
confidence: 99%